DARI PRASANGKA HINGGA DISKRIMINASI: MENYOAL STIGMA SESAT DAN KEKERASAN TERHADAP AHMADIYAH DALAM PERSPEKTIF KOMUNIKASI - Halimatusa’diah Halimatusa’diah (Avant Garde, 2017)
Ahmadiyya as a minor belief is not a new community in Indonesia. Sincereformation era, their existence experiences controversies as well as oppositionsfrom the society. From desk research and literature review method, this paperaims to describe the ways prejudice toward Ahmadiyya community emerge anddraw the role of communication in connecting the major and minor community inIndonesia. This paper discusses the violence against the Ahmadiyya in Indonesiathrough communication perspective. The concept of prejudice expression fromGW Allport (1954) and Samovar (2013) in this paper shows that violenceexperienced by Ahmadiyya is already at the stage of extermination rather thanonly at discrimination stage.